Robotic Surgery may Not “Make the Cut” in Pediatrics - Bruns, Nicholas E.; Soldes, Oliver S.; Ponsky, Todd A. (Frontiers in Pediatrics, 2015)
Since the introduction of robotic surgery in children in 2001, it has been employed by select pediatric laparoscopic surgeons but not to the degree of adult surgical specialists. It has been suggested that the technical capabilities of the robot may be ideal for complex pediatric surgical cases that require intricate dissection. However, due to the size constraints of the robot for small pediatric patients, the tight financial margins that pediatric hospitals face, and the lack of high level data displaying patient benefit when compared to conventional laparoscopic surgery, it may be some time before the robotic surgical platform is widely embraced in pediatric surgical practice.